Pengaruh Value Added Capital Employed, Value Added Human Capital, dan Structural Capital Value Added Terhadap Return On Assets (ROA) pada Bank Umum Syariah di Indonesia periode 2016-2020 - Rena Vidia Hodijah; Iwan Setiawan; Ramadhani Irma Tripalupi (ILTIZAM Journal of Shariah Economics Research, 2023)
The purpose of this study is to determine and analyze the effect of 1)VACA to ROA 2) VAHU to ROA 3) STVA to ROA based on PSAK 19 on Islamic banks in Indonesia. The independent variables in this study are Value Added Capital Employed (VACA) (X1), Value Added Human Capital (VAHU) (X2), and and Structural Capital Value Added (STVA) (X3) and the dependent variable in this study is Return On Assets (ROA) (Y). The method in this study is a quantitative method and uses a descriptive approach. Conducted statistical tests including descriptive analysis, multiple linear analysis, classical assumption test, hypothesis testing consisting of T test and F test and determination analysis. The results in this study according to the T test or partial test stated that 1) VACA (X1) had a positive effect on ROA, 2) VAHU (X2) had a negative effect on ROA, 3) STVA (X3) had a negative effect on ROA. 4) based on the results of the analysis of the F test or simultaneous test, it is stated that VACA (X1), VAHU (X2), STVA (X3) have a positive effect on return on assets (ROA)